Admissions for orthostatic hypotension: an analysis of NHS England Hospital Episode Statistics data - Rose Anne Kenny; Eoin Duggan; Roman Romero-Ortuno (BMJ Open)
Objectives To determine whether admissions for orthostatic hypotension (OH) and its consequences, such as falls, have changed over the past 10 years in the National Health Service (NHS) England.Setting Data from NHS England Hospital Episode Statistics, a database containing details of all admissions, accident and emergency attendances and outpatient appointments at NHS hospitals in England, were obtained and analysed.Participants Data on hospital admissions in NHS England, as defined by finished consultant episodes (FCEs), were examined between 2008 and 2017.Main outcome measures FCEs for the following International Classification of Disease codes were examined: OH (I95.1), tendency to fall (R29.6), epilepsy (G40) and chronic obstructive pulmonary disease (COPD) (J44). The total number of FCEs was also examined.Results Between 2008 and 2017, FCEs for OH rose from 14 658 to 30 759, a 110% increase. The greatest increase was in the over 75 years age group where FCEs went from 10 639 to 22 756, a 114% rise. The number of falls related FCEs in this age group rose from 61 841 to 89 622 (45%). Admissions for epilepsy and COPD rose by 7% and 35%, respectively.Conclusions The number of admissions for OH has risen dramatically over the past 10 years, as have admissions for falls and related disorders. This rise is out of proportion with admissions for other conditions such as epilepsy and COPD. We postulate that this relates to tighter blood pressure (BP) targets. This suggests caution in the application of recent BP targets to older, frailer adults.